The benefits of an anthropological approach in modern management sciences research - Kowalska, Alicja (Contemporary organisation and management. Challenges and trends, 2020)
How do new managerial models and socio-economic change impact the methodology of management sciences? The author aims to answer how best to describe and analyse the challenges of modern organization and their management system in light of the needs and expectations of employees. The goal of this article is to emphasize the necessity and the benefits of an anthropological approach in management sciences research. The author will present the concepts and methods of social, business and corporate anthropology as a framework for the scientific exploration of the technological revolution that influences various levels of human mentality and attitudes in a workplace.